Transformational leadership in Slovak teachers compared to Slovak managers - Ďuricová, Lenka (Psihološka obzorja (Ljubljana), 2022)
Based on the need to reform the Slovak education system, it is useful to review teachers in the role of potential leaders whose task within the system is to contribute to positive change. The paper presents an analysis of differences in transformational leadership styles between Slovak secondary school teachers and Slovak managers. The research sample, obtained by the method of intentional and available selection, consisted of teachers in secondary education (n = 142) and managers in the manufacturing sector at various levels of management (n = 117). The data was obtained using the Slovak version of the LPI / Leadership Practices Inventory (Kouzes & Posner, 2017), the five dimensions of which showed satisfactory internal consistency in both groups of respondents (Cronbach ? from .65 to .84). The results of the leadership style comparisons using the Kouzes and Posner LPI indicate statistically significant differences in favour of Slovak teachers compared to Slovak managers in all dimensions except ‘Enable others to act’. The results are discussed in terms of the respondents’ gender, their length of practice and the nature of their job. The research study is limited mainly by the size of the sample, its selection and the use of self-assessment scales.
Keywords: Leadership practices inventory LPI; managers; menedžerji; Slovakia; Slovaška; teachers; transformacijsko vodenje; transformational leadership; učitelji